The clinical spectrum of reversible cerebral vasoconstriction syndrome: The Italian Project on Stroke at Young Age (IPSYS). (September 2019) - Caria, Filomena; Zedde, Marialuisa; Gamba, Massimo; Bersano, Anna; Rasura, Maurizia; Adami, Alessandro; Piantadosi, Carlo; Quartuccio, Luca; Azzini, Cristiano; Melis, Maurizio; Luisa Delodovici, Maria; Dallocchio, Carlo; et al.
Introduction: To describe clinical, neuroimaging, and laboratory features of a large cohort of Italian patients with reversible cerebral vasoconstriction syndrome. Methods: In the setting of the multicenter Italian Project on Stroke at Young Age (IPSYS), we retrospectively enrolled patients with a diagnosis of definite reversible cerebral vasoconstriction syndrome according to the International Classification of Headache Disorders (ICHD)-3 beta criteria (6.7.3 Headache attributed to reversible cerebral vasoconstriction syndrome, imaging-proven). Clinical manifestations, neuroimaging, treatment, and clinical outcomes were evaluated in all patients. Characteristics of reversible cerebral vasoconstriction syndrome without typical causes ("idiopathic reversible cerebral vasoconstriction syndrome") were compared with those of reversible cerebral vasoconstriction syndrome related to putative causative factors ("secondary reversible cerebral vasoconstriction syndrome"). Results: A total of 102 patients (mean age, 47.2 ± 13.9 years; females, 85 [83.3%]) qualified for the analysis. Thunderclap headache at presentation was reported in 69 (67.6%) patients, and it typically recurred in 42 (60.9%). Compared to reversible cerebral vasoconstriction syndrome cases related to putative etiologic conditions (n = 21 [20.6%]), patients with idiopathic reversible cerebral vasoconstriction syndrome (n = 81 [79.4%]) were significantly older (49.2 ± 13.9 vs. 39.5 ± 11.4 years), had more frequently typical thunderclap headache (77.8% vs. 28.6%) and less frequently neurological complications (epileptic seizures, 11.1% vs. 38.1%; cerebral infarction, 6.1% vs. 33.3%), as well as concomitant reversible brain edema (25.9% vs. 47.6%). Conclusions: Clinical manifestations and putative etiologies of reversible cerebral vasoconstriction syndrome in our series are slightly different from those observed in previous cohorts. This variability might be partly related to the coexistence of precipitating conditions with a putative etiologic role on disease occurrence.